Taskscapes, Landscapes, and the Politics of Agricultural Production in Roman Mosaics - Kilian Mallon (Theoretical Roman Archaeology Journal, 2021)
In recent years archaeologists have put forward explanations of the design and impact of mythological and allegorical scenes in mosaics as part of elite Roman visual culture. While scenes of labor have served as evidence to accompany archaeological data on rural life, depictions of labor have received comparatively less attention as part of Roman ideological structures. Through an analysis of mosaics of the imperial period, this article demonstrates the value of adapting Timothy Ingold’s concept of ‘taskscape’ for explaining shared similarities in the communication strategies underlying depictions of agricultural work in Roman art and showcases an approach to the Roman economy rooted in this body of anthropological theory. Elites were able to reinforce normative values about the agricultural world by controlling not just what was seen, but what was not seen. Their mosaics present certain generic and hidden views of work that allowed fellow elites to use their own imaginations to continually ‘fill in the gaps’ and reinforce their control over agricultural production, a strategy that endured across the Roman world for generations.